Need for cognition of first year students at Chulalongkorn University. Chula - Asayaporn, P.; Nimnuan, C. (Chulalongkorn Medical Journal, 2023)
Background : Need for cognition is a tendency of an individual to prefer activities that require thinking process. As a personal attribute, it is interesting to explore need for cognition and its associating factors among students of Chulalongkorn University. The result of this study can then be used for promoting students’ academic performances. Objective : To study need for cognition of first year students of Chulalongkorn University Design : A cross - sectional descriptive study Setting : Chulalongkorn University Materials and Methods : Data were collected from 840 first year undergraduate students of Chulalongkorn University. The research instruments were a demographic questionnaire and need for cognition questionnaire. The data were analyzed using descriptive statistics, independent t-test, one-way ANOVA and multiple linear regression analysis where appropriate. Results : The study shows that the majority the sample group has high need for cognition. Male students require more need of cognition than female students (B = -1.39, p = .001, 95%CI = -2.20, -.58). Students in Science and Technology are more influenced on need for cognition, compared with to students in Health Science (B =2.201, p = <.001, 95%CI = 1.22, 3.18). Students with higher GPAX would have more need for cognition, among the sample group (B =.601, p = .056, 95%CI = -.02, 1.22). Conclusion : Students have high need for cognition and the major factors that predicted need for cognition are gender, faculty and GPAX